Language Shift and Endangerment of Sundanese Banten Dialect in South Tangerang - Umi Kulsum; Azhari Dasman Darnis; Adang Asdari (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2023)
The objective of this research is to find out the language shift in one of Sundanese dialects known as Bantenese (SBD) and the reasons underlied, in the spoken area of South Tangerang, which could bring to endangered of extinction. The SBD is spoken by the native in South Tangerang in several areas along Cisadane river which is adjacent to Tangerang district. The observation was carried out on two things, namely the use of SBD words among the native speakers and the use of Sundanese among children. This is a qualitative-descriptive research using participant observation and informal interviews. Observations were made in six sub-districts, where the majority of the native people are Sundanese. The observation involved observation, interview, taking notes, and recording techniques. The results showed that there was language shift in SBD among the Sundanese ethnic population in South Tangerang. The main reason is the negative perspective of speakers of SBD. As the consequence, the language is not transmitted to next generation thus led to endangerement.